2021
DOI: 10.1002/smll.202007909
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Growth of Large‐Sized and Phase‐Selectivity 2D GaTe Crystals

Abstract: Since the first discovery of graphene obtained by mechanical exfoliation (ME) in 2004, [1] 2D layered materials have been widely investigated due to their unique electrical, optical, and mechanical properties at the single atomic thickness. [2,3] In the past decade, substantial progress has been made toward the use of 2D materials for next-generation electronic devices, [4] GaTe has recently attracted significant interest due to its direct bandgap and unique phase structure, which makes it a good candidate for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 39 publications
0
21
0
1
Order By: Relevance
“…[4][5][6] On the other hand, the m-GaTe phase is more thermodynamically stable than the h-GaTe phase; thus, it is commonly observed in epitaxial growth such as chemical vapor deposition (CVD), physical vapor deposition (PVD), and molecular beam epitaxy (MBE). [7][8][9] For instance, Huynh et al have demonstrated diversity of the 2D-GaTe nanostructures on GaAs (001) substrates by MBE. Interestingly, the study has proposed a great selectivity to achieve single-phase h-GaTe as deposited on the GaN/sapphire substrate.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] On the other hand, the m-GaTe phase is more thermodynamically stable than the h-GaTe phase; thus, it is commonly observed in epitaxial growth such as chemical vapor deposition (CVD), physical vapor deposition (PVD), and molecular beam epitaxy (MBE). [7][8][9] For instance, Huynh et al have demonstrated diversity of the 2D-GaTe nanostructures on GaAs (001) substrates by MBE. Interestingly, the study has proposed a great selectivity to achieve single-phase h-GaTe as deposited on the GaN/sapphire substrate.…”
Section: Introductionmentioning
confidence: 99%
“…10 Note that the broadening in linewidth of these peaks in the spectrum of the 350 °C sample could be due to its poor crystal quality, as discussed in the following section. This kind of spectrum assumedly points to the dominant existence of the h-GaTe phase in the film 8,9,16 in considering a low density of m-GaTe nanorods as observed from SEM images (Figure 1a,b). As T g gets higher than 400 °C, the m-GaTe characteristic peaks positioned at ∼58, 64, 74, 109, 114, 161, 172, 196, 209, 270, and 285 cm −1 were more and more visible.…”
Section: Resultsmentioning
confidence: 63%
“…The Raman spectrum of the 15 min sample (Figure 5e) is well recognized with the thoroughly dominant phonon modes at ∼126 and ∼141 cm −1 , similar to that of the GaTe/GaN/sapphire sample (Figure 4e) or ultrathin single-crystal h-GaTe flakes in most recent studies using other growth methods. 8,16 Accordingly, it is worth noting that this motif of the Raman pattern featured by these phonon modes may represent either the presence of single-phase h-GaTe nanostructures or the lateral h/m-mixed GaTe phase in a structural thin film.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations